2020
DOI: 10.3174/ajnr.a6747
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Imaging of Third Molar–Related Abnormalities

Abstract: Third molars may be associated with a wide range of pathologic conditions, including mechanical, inflammatory, infectious, cystic, neoplastic, and iatrogenic. Diagnosis of third molar-related conditions can be challenging for radiologists who lack experience in dental imaging. Appropriate imaging evaluation can help practicing radiologists arrive at correct diagnoses, thus improving patient care. This review discusses the imaging findings of various conditions related to third molars, highlighting relevant ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…(Poblete et al, 2020) As described in the literature, some of the main characteristics that increase the difficulty of surgery are the roots due to the chance of being fused, thin, without a conventional anatomical shape, making extraction more complex. (Loureiro et al, 2020) At the level of the coronal diameter it seems to be similar to that of the lower first and second molars.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…(Poblete et al, 2020) As described in the literature, some of the main characteristics that increase the difficulty of surgery are the roots due to the chance of being fused, thin, without a conventional anatomical shape, making extraction more complex. (Loureiro et al, 2020) At the level of the coronal diameter it seems to be similar to that of the lower first and second molars.…”
Section: Introductionmentioning
confidence: 77%
“…Glera-Suárez et al, 2020)(Jaroń et al, 2020)(Kim et al, 2018)(Konkel et al, 2019)(Loureiro et al, 2020)(Mahardawi et al, 2020)(Marinkovic et al, 2020) to surgery Complications of lower third molars before supernumerary teeth. Pharmacotherapy after extraction.…”
mentioning
confidence: 99%
“…This study excluded third molars because third molars have larger variations among different populations [ 19 ]. In addition, the third molars may be removed due to neoplastic, infectious, inflammatory, iatrogenic, cystic and other conditions [ 20 ]. Premolars were added to this study and were excluded by some studies [ 21 , 22 ] because premolars (except the first maxillary premolar) usually do not have more root bifurcations and are thought to have a small chance of taurodontism (0.79%) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors have been reported to be associated with CRS, including anatomic abnormalities, immune dysfunction, host genetics, and microbial dysbiosis 15 , 23 . Odontogenic rhinosinusitis is usually diagnosed when a CT scan indicates a bone defect in the maxillary sinus floor, and odontogenic rhinosinusitis is typically associated with an infection of dental origin 24 . Through metagenomics analysis, Lucas et al reported that anaerobic microbiota plays a crucial virulence role in CRS; they also revealed that a mucin-degrading anaerobic microbial consortium, composed of Prevotella , Fusobacterium , and Streptococcus , enhances the virulence of CRS–related S. aureus 25 .…”
Section: Discussionmentioning
confidence: 99%